TRIM21: a cytosolic Fc receptor with broad antibody isotype specificity. Issue 1 (November 2015) - Foss, Stian; Watkinson, Ruth; Sandlie, Inger; James, Leo C.; Andersen, Jan Terje
Summary: Antibodies are key molecules in the fight against infections. Although previously thought to mediate protection solely in the extracellular environment, recent research has revealed that antibody‐mediated protection extends to the cytosolic compartment of cells. This postentry viral defense mechanism requires binding of the antibody to a cytosolic Fc receptor named tripartite motif containing 21 (TRIM21). In contrast to other Fc receptors, TRIM21 shows remarkably broad isotype specificity as it does not only bind IgG but also IgM and IgA. When viral pathogens coated with these antibody isotypes enter the cytosol, TRIM21 is rapidly recruited and efficient neutralization occurs before the virus has had the time to replicate. In addition, inflammatory signaling is induced. As such, TRIM21 acts as a cytosolic sensor that engages antibodies that have failed to protect against infection in the extracellular environment. Here, we summarize our current understanding of how TRIM21 orchestrates humoral immunity in the cytosolic environment.